UMA ANÁLISE DO PERFIL DOS PROFESSORES DE QUÍMICA E DOS ALUNOS NA EDUCAÇÃO BÁSICA - Vitória Dos Santos Lima, Alessa; Dutra Gonçalo, Fernando Henrique; Oliveira Andrade Flor, Henrique; Tavares Cunha, Jose Diego; Ferreira Maia, Rafaella; Waskiton Moura Valentin, Raquel; Nunes Teixeira, Ronaldo; Gonçalves Bertolli, Sara; Gonçalves Barbosa, Hellen Franciane (Intercursos, 2026)
não há